The Level and Nature of Impairment on the Iowa Gambling Task Following Acquired Brain Injury: A Meta-analysis - Sammy Moore; Kristin Naragon-Gainey; Carmela F. Pestell; Rodrigo Becerra; Melissa T. Buelow; Danielle M. Fynn; Michael Weinborn (Neuropsychology Review, 2026)
The Iowa Gambling Task (IGT) is a popular measure of risky decision-making, but to date, no formal quantitative reviews have been conducted, focused exclusively on IGT performance amongst individuals with acquired brain injury (ABI). Therefore, this meta-analytic study firstly explored performance differences between individuals with ABI vs controls. Second, we extended this comparison by investigating differences in IGT scoring and interpretive approaches (e.g., total score vs later block analysis). Finally, we explored potential IGT performance moderators (e.g., average age). A total of 25 studies, containing 39 samples (total n = 2188), were included. Overall findings suggested that the IGT is sensitive to the presence of ABI, particularly non-TBI and medically confirmed TBI, which becomes evident by block 2 of 5. Medium effect sizes were obtained for IGT total score, as well as indicators using later blocks only. Performance moderators such as population type and region influenced IGT performance, whilst average age, average education, and proportion of males did not. These results indicate that the IGT is sensitive to decision-making impairment following ABI, although we conclude that further research is needed to confirm the IGT’s ability to detect impairment relative to specific brain regions.